Atropinic (anticholinergic) burden in antipsychotic‐treated patients. (27th September 2017) - Montastruc, François; Benevent, Justine; Touafchia, Anthony; Chebane, Leila; Araujo, Mélanie; Guitton‐Bondon, Emmanuelle; Durrieu, Geneviève; Arbus, Christophe; Schmitt, Laurent; Begaud, Bernard; Montastruc, Jean‐Louis
Abstract: Antipsychotic drugs possess side atropinic (anticholinergic) properties that may induce several adverse drug reactions (ADRs), such as memory loss or cognitive impairment. The aim of this study was to investigate anticholinergic burden in patients treated with antipsychotic drugs. All ADR reports including at least one antipsychotic and registered between 2000 and 2015 in the Midi‐Pyrénées PharmacoVigilance Database were extracted and analyzed using the Anticholinergic Duran's list. The primary objective of this cross‐sectional study was to calculate anticholinergic burden in antipsychotic‐treated patients; the secondary one was to investigate associated factors. Among the 1948 reports, the average number of atropinic drugs per report was 2.4 ± 1.4. At least one atropinic drug was found in 59.4% of reports (1158), in addition to antipsychotic drugs. The mean anticholinergic burden per report was 3.9 ± 2.9. A value ≥3 was found in 61.7% of the reports. A significant association between anticholinergic burden, age, and male gender of patients was found. The mean value of anticholinergic burden remained stable during the study period. This study showed high values of anticholinergic burden in patients receiving antipsychotics. Thus, considering the potential noxious clinical impact of atropinic properties on cognitive functions, an appropriate approach should be used to reduce prescription of antipsychotics with a high anticholinergic burden but also coprescription of other frequently associated atropinic drugs, such as antiparkinsonians, H1 antihistamines, or imipraminic antidepressants in these patients.